2017
DOI: 10.7566/jpsj.86.063704
|View full text |Cite
|
Sign up to set email alerts
|

Strong-Coupling Superconductivity in BaPd2As2 Induced by Soft Phonons in the ThCr2Si2-Type Polymorph

Abstract: The specific heat of two polymorphs of BaPd 2 As 2 was measured. The ThCr 2 Si 2 -type polymorph (space group I4/mmm, D 17 4h , No. 139) is a previously reported superconductor with a transition temperature T c ≃ 3.5 K, while the CeMg 2 Si 2 -type polymorph (P4/mmm, D 1 4h , No. 123) is a normal metal and does not exhibit superconductivity down to 1.8 K. Our results revealed that the ThCr 2 Si 2 -type has an anomalously low Debye temperature, indicative of soft phonons, compared to the CeMg 2 Si 2 -type. Moreo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
3
12
1
Order By: Relevance
“…Debye temperature extracted from the QHDA and elastic constants are almost identical. It should be noted that both Kudo et al [11] and Abdel-Hafiez et al [15] have obtained θ D from the analysis of experimental heat capacity data which turns out to be ~ 144 K. This value is significantly lower than the value obtained in this study. Chen et al [14], on the other hand, has calculated the Debye temperature from the analysis of phonon dispersion and found a value of 213 K. Johnston et al [46] have found θ D = 273 K from low-T fit to the heat capacity data.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Debye temperature extracted from the QHDA and elastic constants are almost identical. It should be noted that both Kudo et al [11] and Abdel-Hafiez et al [15] have obtained θ D from the analysis of experimental heat capacity data which turns out to be ~ 144 K. This value is significantly lower than the value obtained in this study. Chen et al [14], on the other hand, has calculated the Debye temperature from the analysis of phonon dispersion and found a value of 213 K. Johnston et al [46] have found θ D = 273 K from low-T fit to the heat capacity data.…”
Section: Discussioncontrasting
confidence: 69%
“…Chen [14] carried out lattice dynamical calculations to study the electron-phonon coupling and its relevance to superconductivity in BaPd 2 As 2 at relatively higher temperature. Kudo et al [11] found a high electron phonon coupling constant (λ e-ph ), dominated by soft phonon modes in this SC compound. Very recently Abdel-Hafiez et al [15] studied the physical properties of BaPd 2 As 2 under pressure both experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The compounds with lower Debye temperature tend to show higher T c . For instance, BaPd 2 As 2 shows superconductivity below ∼3.5 K with the Debye temperature being ∼140 K while T c of SrPd 2 As 2 is ∼1 K with the Debye temperature of ∼300 K. The estimated specific heat γ values of these compounds are very close to each other [23], suggesting that the density of states of the two compounds can be comparable. Hence it has been discussed that the presence of soft phonon may enhance electron-phonon interaction (λ) in the phonon-mediated superconductivity.…”
Section: Introductionmentioning
confidence: 80%
“…As a matter of fact, superconductivity also appears in the nonmagnetic CT phase of 122 materials when Fe atoms are completely substituted by other metals, although the superconducting transition temperature (T c ) remains relatively low [14][15][16][17][18][19][20][21][22][23]. Recently, an interesting relationship between the Debye temperature and T c has been found in Pd-based 122 type of CT arsenide [23]. The compounds with lower Debye temperature tend to show higher T c .…”
Section: Introductionmentioning
confidence: 99%